Baechtold's best Afghanistan the ultimate visual travel guide. (New York, NY Abrams Image, an imprint of Harry N. Abrams, Inc., 2006)
Planning a trip to Afghanistan? Bring a Baechtold!

Baechtold's Best is a revolutionary concept in travel guides for both the adventurous traveler and the arm-chair variety. Created exclusively using images and maps, Baechtold introduces the traveler to the best of what each country has to offer. Most guides boast encyclopedic ambitions and fill their pages with lengthy descriptions. By contrast, Baechtold guides are created on the premise that one good photograph and an address are enough to point the intrepid traveler in the right direction.

Each guide consists of four categories of destinations (People, Nature, Art, and Things) accompanied by a map to get you there. For each subject, Baechtold offers a number of choices and then designates a "best" the country has to offer.

For Afghanistan a traveler can learn where to find the best field for picking poppy flowers, the sandstorm that packs the most punch, and the perfect watermelon stand. Included are not only the best hotels and restaurants, but the places where the skies are the bluest, the jeeps the rustiest, and the kids the cutest.

Both humorous and helpful, the Baechtold's Best are essential to every traveler aiming to see more of Afghanistan than what's on TV.
Keywords: Afghanistan -- Guidebooks; Afghanistan -- Pictorial works; Afghanistan -- Maps